2022
DOI: 10.1128/jvi.01888-21
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 Inhibits Viral Infection by Promoting MicroRNA-155 Expression

Abstract: Gga-miR-155-5p acts as an important antivirus factor against IBDV infection, which causes a severe immunosuppressive disease in chicken. Elucidation of the mechanism regulating gga-miR-155-5p expression in IBDV-infected cells is essential to our understandings of the host response against pathogenic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Cellular assays confirmed that MDA5, TBK1, and IRF7 are required for GATA3 expression in poly(I:C) host cells. IBDV induces GATA3 expression via the MDA5-TBK1-IRF7 signaling pathway, inhibiting GATA3-mediated gga-miR-155-5p expression during IBDV replication ( 107 ). TLR3 appears central to regulating disease in patients with DM.…”
Section: Ncrnas Role and Mechanism In Melanoma Differentiation-associ...mentioning
confidence: 99%
“…Cellular assays confirmed that MDA5, TBK1, and IRF7 are required for GATA3 expression in poly(I:C) host cells. IBDV induces GATA3 expression via the MDA5-TBK1-IRF7 signaling pathway, inhibiting GATA3-mediated gga-miR-155-5p expression during IBDV replication ( 107 ). TLR3 appears central to regulating disease in patients with DM.…”
Section: Ncrnas Role and Mechanism In Melanoma Differentiation-associ...mentioning
confidence: 99%
“…It was found that upon IBDV infection, the expression of GATA-binding protein (GATA) 3 in DF-1 cells markedly increased; this was attributable to the recognition of viral dsRNA by cellular MDA5, subsequently initiating TBK1-IRF7 signaling pathways, thereby promoting GATA3 expression ( Figure 2 ). Phosphorylated GATA3 translocated to the nucleus where it directly bound to the gga-miR-155 promoter, regulating the expression of gga-miR-155 in IBDV-infected or poly (I:C)-treated DF-1 cells [ 130 ]. GATA3 belongs to the GATA-binding protein family, which plays a crucial role in physiological and pathological processes by directly initiating or restricting the transcription of target genes; GATA3, especially, serves as a key transcription factor driving the differentiation of Th2 cells [ 131 , 132 ].…”
Section: Host Response To Ibdv Infection At the Rna Levelmentioning
confidence: 99%
“…Furthermore, our data show that GATA3 inhibited IBDV replication by promoting the expression gga-miR-155, suppressing IBDV replication by enhancing type I IFN expression ( Figure 2 ). These findings indicate that the transcription factor GATA3 plays a critical role in the host antiviral response by promoting gga-miR-155 expression, which deciphers how the expression of a specific miRNA is regulated in host cells with pathogenic infection; moreover, they remarkably further our understanding of the mechanism of the host response against IBDV infection at the RNA level [ 130 ].…”
Section: Host Response To Ibdv Infection At the Rna Levelmentioning
confidence: 99%